Chemokines in patients with Alzheimer's disease: A meta-analysis - Wang, Hecheng; Zong, Yu; Zhu, Lei; Wang, Weiyi; Han, Yanshuo (Frontiers in Aging Neuroscience, 2023)
Background Alzheimer's disease (AD) is the most common neurodegenerative disease in elderly people. Many researches have reported that neuroinflammation is related to AD. Chemokines are a class of small cytokines that play important roles in cell migration and cell communication, which involved in neuroinflammation. Up to now there is no meta-analysis to explore the difference of chemokines between AD patients and healthy elderly individuals. Method We searched PubMed, Web of science, Cochrane library, EMBASE and Scopus databases from inception to January 2022. Data were extracted by two independent reviewers, and the Review Manager 5.3 was used for the meta-analysis. Result Thirty-two articles were included and analyzed. The total number of participants in the included study was 3,331. We found that the levels of CCL5 (SMD = 2.56, 95% CI: 1.91–3.21), CCL15 (SMD = 3.30, 95% CI: 1.48–5.13) and IP-10 (SMD = 3.88, 95% CI: 1.84–5.91) in the plasma of AD patients were higher than healthy people. MCP-1 protein (SMD = 0.67, 95% CI: 0.29–1.05) in the AD patients' CSF was higher than healthy controls. Conclusion These results suggested that chemokines may play an important role in AD. These findings could provide evidences for the diagnosis and treatment of AD. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021278736, identifier: CRD42021278736.